Formal and Informal Communication Strategies for Public Support in Riau Hijau Policy Implementation - Amir Syamsuadi; Kinanti Indah Safitri; Bela Putri Anjani; Lutfan Jaes; Riki Rahman (FAKULTAS DAKWAH UIN SALATIGA, 2025)
The Riau Hijau policy is a strategic initiative by the Riau Provincial Government to address the environmental crisis and promote sustainable development. However, the success of this policy’s implementation largely depends on the effectiveness of the government’s communication strategy in building public support. This study aims to analyze the local government's communication strategies in socializing and internalizing the Riau Hijau policy among the public and bureaucracy. Using a descriptive qualitative approach, data were collected through document analysis, participatory observation, and in-depth interviews. This study also employed content analysis and bibliometrics using VOSviewer. The findings reveal that Riau Hijau’s communication strategy is divided into two main approaches: formal communication through institutional channels, policy publications, and coordination forums, and informal communication through the activation of local communities, visual narrative-based campaigns, and civil society participation. These findings affirm that two-way participatory communication can build social legitimacy and strengthen collective support for environmental policy.